HarvestPlus Uganda Counting the Gains: Accelerating Nutrition and Public Health with Biofortified Crops - International Potato Center (2016)
We have built the capacity of over 30 vine suppliers to manage their businesses, and supply NGOs, government and local communities. Through partnership with local governments, women and caregivers have accessed planting material through demonstration gardens managed by health centres. Masindi district has developed a district nutrition action plan and ordinance requiring each household to grow orange sweetpotato on a quarter of the home garden.